A new phylogenetic hypothesis of turtles with implications for the timing and number of evolutionary transitions to marine lifestyles in the group - Evers, S; Benson, R (Wiley, 2018)
Evolutionary transitions to marine habitats occurred frequently among Mesozoic reptiles. Only one such clade survives to the present: sea turtles (Chelonioidea). Other marine turtles originated during the Mesozoic, but uncertain affinities of key fossils have obscured the number of transitions to marine life, and the timing of the origin of marine adaptation in chelonioids. Phylogenetic studies support either a highly‐inclusive chelonioid total‐group including fossil marine clades from the Jurassic and Cretaceous (e.g. protostegids, thalassochelydians, sandownids) or a less inclusive chelonioid total‐group excluding those clades. Under this paradigm, these clades belong outside Cryptodira, and represent at least one additional evolutionary transition to marine life in turtles. We present a new phylogenetic hypothesis informed by high resolution computed tomographic data of living and fossil taxa. Besides a well‐supported Chelonioidea, which includes protostegids, we recover a previously unknown clade of stem‐group turtles, Angolachelonia, which includes the Late Jurassic thalassochelydians, and the Cretaceous–Palaeogene sandownids. Accounting for the Triassic Odontochelys, our results indicate three independent evolutionary transitions to marine life in non‐pleurodiran turtles (plus an additional two‐three in pleurodires). Among all independent origins of marine habits, a pelagic ecology only evolved once, among chelonioids. All turtle groups that independently invaded marine habitats in the Jurassic–Cretaceous (chelonioids, angolachelonians, bothremydid pleurodires) survived the Cretaceous–Palaeogene mass extinction event. This highlights extensive survival of marine turtles compared to other marine reptiles. Furthermore, deeply‐nested clades such as chelonioids are found by the middle Early Cretaceous, suggesting a rapid diversification of crown‐group turtles during the Early Cretaceous.